Evaluation of resin composite staining by beverages with acid pH - Rayssa Amaral VIEIRA; Isabella Henriques De Paula VIEIRA; Letícia Cabido PRATA; Wellington Dorigheto Andrade VIEIRA; Diogo de Azevedo MIRANDA (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Introduction: Composite resins are an extensively used esthetic material that has excellent adaptation, reproduces the characteristics of the tooth structure and is suitable for the conditions of the oral environment. However, this material is also very susceptible to staining due to pigmentation coming from the diet and habits of the patient. Objectives: To evaluate the staining of two brands of composite resin, one nanoparticle and a nanohybrid type (Filtek Z350XT® and IPS Empress Direct®), in direct contact with the acid pH of beverages. Methods: In total 40 specimens were made, 20 of each type of resin studied. After being inserted into a Teflon matrix and light activated, the samples were removed, stored in containers with 2 ml of artificial saliva and kept in the refrigerator. Every day 20 of these samples were placed in direct contact with 2 ml Gatorade, and the other 20 samples, in 2 ml of wine, each set for 30 minutes. After 30 minutes, the acid pH substances were removed, and 2 ml of artificial saliva was again placed in the container. This process was repeated every day for 10 days. Results: The results showed that the nanoparticle resin (Filtek Z350XT) was more susceptible to staining than the nanohybrid type (Empress Direct®) when in contact with the wine. When wine and Gatorade were compared, the solution with higher staining capacity was shown to be wine. Conclusion: The two resins tested were susceptible to staining in a 10-day period. Mottling and more staining was visibly detected after samples were immersed in the solution with the higher pH, and nanoparticulate resin was more susceptible to staining.